Digital Light - Cubitt, Sean (Fibreculture Books, 2015)
Light symbolises the highest good, it enables all visual art, and today it lies at the heart of billion-dollar industries. The control of light forms the foundation of contemporary vision. Digital Light brings together artists, curators, technologists and media archaeologists to study the historical evolution of digital light-based technologies. Digital Light provides a critical account of the capacities and limitations of contemporary digital light-based technologies and techniques by tracing their genealogies and comparing them with their predecessor media. As digital light remediates multiple historical forms (photography, print, film, video, projection, paint), the collection draws from all of these histories, connecting them to the digital present and placing them in dialogue with one another. Light is at once universal and deeply historical. The invention of mechanical media (including photography and cinematography) allied with changing print technologies (half-tone, lithography) helped structure the emerging electronic media of television and video, which in turn shaped the bitmap processing and raster display of digital visual media. Digital light is, as Stephen Jones points out in his contribution, an oxymoron: light is photons, particulate and discrete, and therefore always digital. But photons are also waveforms, subject to manipulation in myriad ways. From Fourier transforms to chip design, colour management to the translation of vector graphics into arithmetic displays, light is constantly disciplined to human purposes. In the form of fibre optics, light is now the infrastructure of all our media; in urban plazas and handheld devices, screens have become ubiquitous, and also standardised. This collection addresses how this occurred, what it means, and how artists, curators and engineers confront and challenge the constraints of increasingly normalised digital visual media. While various art pieces and other content are considered throughout the collection, the focus is specifically on what such pieces suggest about the intersection of technique and technology. Including accounts by prominent artists and professionals, the collection emphasises the centrality of use and experimentation in the shaping of technological platforms. Indeed, a recurring theme is how techniques of previous media become technologies, inscribed in both digital software and hardware. Contributions include considerations of image-oriented software and file formats; screen technologies; projection and urban screen surfaces; histories of computer graphics, 2D and 3D image editing software, photography and cinematic art; and transformations of light-based art resulting from the distributed architectures of the internet and the logic of the database. Digital Light brings together high profile figures in diverse but increasingly convergent fields, from academy award-winner and co-founder of Pixar, Alvy Ray Smith to feminist philosopher Cathryn Vasseleu.